Design and development of high precision four roll CNC roll bending machine and automatic control model - Yigang Jing; Shangsheng Jiang; Qun Sun; Ying Zhao; Zhihao Song; Xiangyan Meng; Hengzhen Li (Scientific Reports, 2023)
Abstract In recent years, advancements in industries such as aerospace, military weaponry, automobiles, locomotives, and shipbuilding have led to a surge in the demand for bent and rolled components, along with increasingly stringent requirements for rolling precision. However, the traditional hydraulic cylinder feeding solution has hindered further enhancements in the accuracy of rolled profile contours. Additionally, owing to variations in profile specifications, material properties, and an assortment of random factors during the forming process, the applicability of existing forming formulas remains limited, rendering them suitable only for profile processing under specific circumstances. To address these challenges, servo electric cylinders have been introduced as a replacement for traditional hydraulic cylinders, and the mechanical structure of a four-roll bending machine has been re-engineered. This innovation has demonstrated the feasibility of employing servo electric cylinders in four-roll CNC bending machines for profile bending, resulting in higher control precision and faster response times, ultimately providing a comprehensive design solution for four-roll CNC bending machines. In response to the limited universality of existing forming formulas, the actual R (profile forming curvature) and d (servo electric cylinder feed) values from the four-roll CNC bending machine have been utilized, and curve fitting methods have been implemented as the foundation for the automatic control model. This approach offers a high degree of universality, making it suitable for a wide range of applications. Moreover, as the number of trials increased, forming precision progressively improved.